Distinctive waves of innate immune response in the retina in experimental autoimmune encephalomyelitis - Andrés Cruz-Herranz; Frederike C. Oertel; Kicheol Kim; Ester Cantó; Garrett Timmons; Jung H. Sin; Michael Devereux; Nicholas Baker; Brady Michel; Ryan D. Schubert; Lakshmisahithi Rani; Christian Cordano; et al. (JCI Insight, 2021)
Neurodegeneration mediates neurological disability in inflammatory demyelinating diseases of the CNS. The role of innate immune cells in mediating this damage has remained controversial with evidence for destructive and protective effects. This has complicated efforts to develop treatment. The time sequence and dynamic evolution of the opposing functions are especially unclear. Given limits of in vivo monitoring in human diseases such as multiple sclerosis (MS), animal models are warranted to investigate the association and timing of innate immune activation with neurodegeneration. Using noninvasive in vivo retinal imaging of experimental autoimmune encephalitis (EAE) in CX3CR1GFP/+–knock-in mice followed by transcriptional profiling, we are able to show 2 distinct waves separated by a marked reduction in the number of innate immune cells and change in cell morphology. The first wave is characterized by an inflammatory phagocytic phenotype preceding the onset of EAE, whereas the second wave is characterized by a regulatory, antiinflammatory phenotype during the chronic stage. Additionally, the magnitude of the first wave is associated with neuronal loss. Two transcripts identified — growth arrest–specific protein 6 (GAS6) and suppressor of cytokine signaling 3 (SOCS3) — might be promising targets for enhancing protective effects of microglia in the chronic phase after initial injury.